Genetic Targeting of Arginase-II in Mouse Prevents Renal Oxidative Stress and Inflammation in Diet-Induced Obesity - Huang, Ji; Rajapakse, Angana; Xiong, Yuyan; Montani, Jean-Pierre; Verrey, François; Ming, Xiu-Fen; Yang, Zhihong (Frontiers in Physiology, 2016)
Obesity is associated with development and progression of chronic kidney disease (CKD). Recent evidence demonstrates that enhanced levels of the L-arginine:ureahydrolase, including the two isoenzymes arginase-I (Arg-I) and arginase-II (Arg-II) in vascular endothelial cells promote uncoupling of endothelial nitric oxide synthase (eNOS), leading to increased superoxide radical anion and decreased NO production thereby endothelial dysfunction. Arg-II but not Arg-I is abundantly expressed in kidney and the role of Arg-II in CKD is uncertain and controversial. We aimed to investigate the role of Arg-II in renal damage associated with diet-induced obesity mouse model. Wild type (WT) C57BL/6 mice and mice deficient in Arg-II gene (Arg-II-/-) were fed with either a normal chow (NC) or a high-fat-diet (HFD) for 14 weeks (starting at the age of 7 weeks) to induce obesity. In WT mice, HFD feeding caused frequent renal lipid accumulation, enhancement of renal ROS levels which could be attenuated by a NOS inhibitor, suggesting uncoupling of NOS in kidney. HFD feeding also significantly augmented renal Arg-II expression and activity. All the alterations in the kidney under HFD feeding were reduced in Arg-II-/- mice. Moreover, mesangial expansion as analysed by Periodic Acid Schiff (PAS) staining and renal expression of vascular adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) in HFD-fed WT mouse assessed by immunoblotting were reduced in the HFD-fed Arg-II-/- mice, although there was no significant difference in body weight and renal weight/body weight ratio between the WT and Arg-II-/- mice. Thus, Arg-II expression/activity is enhanced in kidney of diet-induced obesity mice. Genetic targeting of Arg-II prevents renal damage associated with obesity, suggesting an important role of Arg-II in obesity-associated renal disease development.